International human rights law and practice - Bantekas, Ilias; Oette, Lutz (Cambridge : Cambridge University Press, 2020)
This unique textbook merges human rights law with its practice, from the courtroom to the battlefield. Human rights are analysed in their particular context, and the authors assess, among other things, the impact of international finance, the role of NGOs, and the protection of rights in times of emergency, including the challenges posed by counter-terrorism. In parallel, a series of interviews with practitioners, case studies and practical applications offer multiple perspectives and challenging questions on the effective implementation of human rights. Although the book comprehensively covers the traditional areas of international human rights law, including its regional and international legal and institutional framework, it also encompasses, through distinct chapters or large sections, areas that have a profound impact on human rights worldwide, such as women's rights, human rights and globalisation, refugees and migration, human rights obligations of non-state actors, debt and human rights, and others.
International human rights law and notions of human rights : foundations, achievements and challenges -- International human rights law : the normative framework -- Human rights in practice -- The United Nations Charter system -- The UN rights treaty system -- Regional human rights treaty systems -- Individual complaints procedures -- Civil and political rights -- Economic, social and cultural rights -- Group rights : self-determination, minorities and indigenous peoples -- The human rights of women -- Children's rights -- The Recognition and protection of the human rights of vulnerable groups and persons -- The right to development and sustainable development -- Victims' rights and reparation -- The application of human rights in armed conflict -- Human rights and international criminal justice -- Human rights and counter-terrorism -- Human rights obligations of non-state actors -- Globalisation and its impact on human rights.
Title from publisher's bibliographic system (viewed on 08 Dec 2020).
Keywords: elektronické knihy; electronic books; Human rights; International law and human rights